Black zirconia composite sintered body and its manufacturing method
By integrating ZrO2, HfO2, Nb2O5, and Ta2O5 with capping elements, the black zirconia composite sintered body achieves improved machinability and productivity, addressing the limitations of existing zirconia sintered bodies in processing efficiency and tool wear.
Patent Information
- Application Number
- JP2024524946
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-06-01
- Filing Date
- 2023-06-01
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-06-01
AI Technical Summary
Existing zirconia sintered bodies face challenges with poor machinability and workability, particularly when used in black form, leading to high processing costs and reduced productivity due to tool wear and long machining times.
Incorporating ZrO2 and HfO2 as stabilizers, along with Nb2O5 and/or Ta2O5, and capping elements or ions such as Cu, Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl, and F into the zirconia composite sintered body, which suppresses phase transitions and enhances machinability by weakening grain boundary strength.
The resulting black zirconia composite sintered body exhibits excellent machinability, allowing for efficient continuous processing with reduced tool wear and increased productivity, while maintaining strength and design aesthetics.
Smart Images

Figure 0007606051000003 
Figure 0007606051000004 
Figure 0007606051000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a black zirconia composite sintered body and a method for producing the same, and more particularly to a black zirconia composite sintered body which is excellent in strength and in the sintered state in terms of workability, and a method for producing the same. [Background technology]
[0002] With the revolution in communication technology such as 5G, the radio waves used for communication are shifting to higher frequency bands. Metal is mainly used for the back plate of 5G compatible smartphones, but since metal is not suitable for transmitters and receivers of radio waves in the high frequency band, plastic, glass, and ceramics are used instead.
[0003] Among these, black ceramics have been used because of their high design value, such as giving a sense of luxury. There was also a need to use zirconia as a highly decorative ceramic. However, zirconia is a material that is difficult to process in the sintered state. Therefore, if zirconia sintered bodies were used as a partial material for smartphones, the processing costs would be high due to the difficulty of processing the sintered bodies.
[0004] Under these circumstances, since black is essential as the color of the housing of a smartphone, black-colored machinable ceramics have been developed by containing zirconia but not making it the main component (for example, Patent Document 1).
[0005] On the other hand, black zirconia sintered bodies have also been developed from the viewpoint of excellent designability, although they are significantly inferior in processability (for example, Patent Documents 2 and 3).
[0006] In addition, as for zirconia sintered bodies, although they are not black and are in the dental field, processable zirconia sintered bodies with improved processability have also been developed (for example, Patent Document 4). For example, Patent Document 4 discloses processable zirconia, which is a sintered body formed so as to contain a tetragonal zirconia composite powder containing 79.8 to 92 mol% ZrO2 and 4.5 to 10.2 mol% Y2O3, 3.5 to 7.5 mol% Nb2O5 or 5.5 to 10.0 mol% Ta2O5, and a TiO2 nanopowder whose mass ratio to the zirconia composite powder is more than 0 mass% and 2.5 mass% or less, and a method for producing the same. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2001-354480 A [Patent Document 2] JP 2006-342036 A [Patent Document 3] JP 2017-77976 A [Patent Document 4] JP 2015-127294 A Summary of the Invention [Problem to be solved by the invention]
[0008] In Patent Document 1, zirconia is used as a black pigment by reduction firing. However, as the content of zirconia increases, the machinability decreases, so the blending ratio of zirconia is low.
[0009] Patent Document 2 proposes a zirconia sintered body with a deep black color. Patent Document 3 also proposes a black zirconia sintered body that addresses the problem of color tone change due to sintering when obtaining the zirconia sintered body.
[0010] However, both Patent Documents 2 and 3 fail to solve the problem of poor processability.
[0011] In addition, the zirconia sintered body disclosed in Patent Document 4 can be machined even in a sintered state. However, it is difficult to say that it has excellent processability, and the processing time for cutting out the processed body is long, so there is still room for improvement in processability. In addition, since it is not black but has excellent translucency, the color tone is completely different. Furthermore, although the zirconia sintered body disclosed in Patent Document 4 can be machined, the number of processed bodies obtained by continuous machining using one machining tool is small, and the machining tool wears quickly, so that the machining tool needs to be replaced more frequently, the tool replacement time increases, and productivity and economy decrease.
[0012] As described above, even in Patent Document 4, the zirconia sintered body is only said to be processable, and since there is a specific problem due to the sintered state of zirconia, that is, the zirconia sintered body is very difficult to process, it remains difficult to provide a zirconia sintered body that has excellent processability in the sintered body state, and a zirconia sintered body that has excellent processability in the sintered body state and is black in color has not been obtained.
[0013] An object of the present invention is to provide a zirconia composite sintered body which has excellent machinability in a sintered state and is black in color. [Means for solving the problem]
[0014] As a result of intensive research into solving the above problems, the inventors have found that the problems can be solved by further containing a capping element or ion in a black zirconia composite sintered body containing ZrO2, HfO2, a stabilizer capable of suppressing the phase transition of zirconia, and Nb2O5 and / or Ta2O5 in predetermined ratios. Based on this finding, the inventors have conducted further research and have completed the present invention.
[0015] That is, the present invention includes the following inventions. [1] A ceramic ceramic material comprising ZrO2, HfO2, a stabilizer capable of suppressing a phase transformation of zirconia, and Nb2O5 and / or Ta2O5; In the case where the total amount of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5 is 100 mol%, The total content of ZrO2 and HfO2 is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%, A black zirconia composite sintered body further containing elements or ions derived from a capping agent. [2] The black zirconia composite sintered body according to [1], wherein the content of elements or ions derived from the capping agent is greater than 0 mol% and less than or equal to 5 mol% relative to a total of 100 mol% of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5. [3] A black zirconia composite sintered body according to [1] or [2], in which a sample 15 mm in diameter and 1.2 mm in thickness is used to measure the color of the sample against a white background using the L*a*b* color system, and the chroma C* calculated from a* and b* is 10 or less. [4] The black zirconia composite sintered body according to [1] or [2], wherein the colorimetric values measured on a sample having a diameter of 15 mm and a thickness of 1.2 mm against a white background using the L*a*b* color system are L*≦60, |a*|≦3, and |b*|≦3. [5] The black zirconia composite sintered body according to any one of [1] to [4], wherein the element or ion derived from the capping agent contains at least one element or ion thereof selected from the group consisting of Cu, Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl, and F. [6] When the content of the stabilizer is A mol%, and the total content of Nb2O5 and Ta2O5 is B mol%, The black zirconia composite sintered body according to any one of [1] to [5], wherein A / B is 0.9 or more and 3 or less. [7] The black zirconia composite sintered body according to any one of [1] to [6], wherein the stabilizer contains Y2O3 and / or CeO2. [8] The black zirconia composite sintered body according to any one of [1] to [7], further comprising a zirconia reinforcing agent, the content of which is more than 0 mass% and not more than 5.0 mass% relative to 100 mass% of the total of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5. [9] The black zirconia composite sintered body according to [8], wherein the zirconia reinforcing agent contains TiO2 and / or Al2O3.
[10] The black zirconia composite sintered body according to [9], wherein the zirconia reinforcing agent contains TiO2 and the TiO2 content is 0.6 to 3.7 mass%.
[11] A ceramic ceramic material comprising ZrO2, HfO2, a stabilizer capable of suppressing a phase transformation of zirconia, and Nb2O5 and / or Ta2O5; In the case where the total amount of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5 is 100 mol%, The total content of ZrO2 and HfO2 is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%, producing a molded body using a raw material composition further containing a capping agent; and sintering the compact. The method for producing a black zirconia composite sintered body according to any one of [1] to
[10] .
[12] The step of sintering the molded body includes a step of reducing and firing the molded body.
[11] A method for producing a black zirconia composite sintered body according to the present invention.
[13] The capping agent contained in the raw material composition is a compound that can become a monovalent ion, The method further includes a step of wet-mixing each of the raw materials of the raw material composition in a solvent containing water to obtain a raw material composition. The method for producing the black zirconia composite sintered body according to
[11] or
[12] .
[14] The method for producing a black zirconia composite sintered body according to any one of
[11] to
[13] , wherein in the raw material composition, the stabilizer includes a stabilizer that is not solid-dissolved in ZrO2 and HfO2. Effect of the Invention
[0016] According to the present invention, it is possible to provide a zirconia composite sintered body which has excellent machinability in a sintered state and is black in color. Furthermore, according to the present invention, a black zirconia composite sintered body can be provided which can be machined in a sintered body state, the machining time required for machining can be short, and wear on the machining tool can be suppressed. A large number of workpieces can be cut out by continuous machining using a single machining tool (hereinafter, also simply referred to as "continuous machining"), and which is therefore highly productive and economical. Furthermore, according to the present invention, a black zirconia composite sintered body having excellent strength and design properties can be provided. Furthermore, according to the present invention, the method for producing the black zirconia composite sintered body does not require pressure sintering. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a schematic diagram showing an estimated structure of the black zirconia composite sintered body of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing a presumed mechanism of action of elements or ions derived from the capping agent of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The black zirconia composite sintered body of the present invention contains ZrO2, HfO2, a stabilizer capable of suppressing a phase transition of zirconia (hereinafter, also simply referred to as a "stabilizer"), and Nb2O5 and / or Ta2O5, In the case where the total amount of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5 is 100 mol%, The total content of ZrO2 and HfO2 is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%, It further contains elements or ions derived from the capping agent.
[0019] The black zirconia composite sintered body of the present invention means that the ZrO2 particles (powder) are in a completely sintered state (sintered state). In this specification, the upper and lower limit values of the numerical ranges (contents of each component, ratios calculated from each component, values, and properties of each component, etc.) can be appropriately combined. In this specification, machining includes cutting and grinding. The mechanical processing may be either wet processing or dry processing, and is not particularly limited.
[0020] In this specification, an element or ion derived from a capping agent (hereinafter also referred to as "capping element or ion") refers to an element or ion that caps the end of a bond of a zirconia-based composite oxide in a black zirconia composite sintered body composed of a zirconia-based composite oxide, thereby weakening the strength (hereinafter also referred to as "grain boundary strength") of a crystal interface (hereinafter also referred to as "grain boundary"). The capping agent is capable of capping a portion of the grain boundaries. The term "capping" refers to a state in which a target element or ion (capping element or ion) is bonded to a bond of the zirconia composite oxide in place of the metal element and is present at the grain boundary. It is presumed that the presence of capping elements or ions at grain boundaries in the form of +1-valent cations or -1-valent anions causes electrostatic repulsion between the capped cations or anions, weakening the grain boundary strength.
[0021] In this specification, the content of each component in the black zirconia composite sintered body can be calculated from the amount of the raw material charged. In addition, the contents of ZrO2, HfO2, the stabilizer, Nb2O5 and Ta2O5 in the black zirconia composite sintered body can also be measured by, for example, inductively coupled plasma (ICP) emission spectrometry, fluorescent X-ray analysis or the like. The content (mol%) of the element or ion derived from the capping agent is the external addition rate relative to the total of 100 mol% of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5. Therefore, the content of the element or ion derived from the capping agent in the black zirconia composite sintered body can be calculated by converting the amount (mass) of the raw material added at the time of addition into mol%. The content (mass%) of the zirconia reinforcement is the external addition rate relative to the total of 100 mass% of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5. Therefore, the content of the zirconia reinforcement in the black zirconia composite sintered body can be calculated from the amount (mass) of the raw material added when it is added.
[0022] The reason why the black zirconia composite sintered body of the present invention has suitable strength and high machinability and can be machined in the sintered body state is not clear, but is presumed to be as follows. In a black zirconia composite sintered body containing ZrO2, HfO2, a stabilizer capable of suppressing the phase transition of zirconia, and Nb2O5 and / or Ta2O5, it is presumed that the presence of capping elements or ions at the crystal grain boundaries causes the capping elements or ions to act in a direction that makes it easier for particles to peel off by reducing the grain boundary strength in the form of +1-valent cations or -1-valent anions, making it easier to cut and improving machinability. The black zirconia composite sintered body of the present invention is presumed to have a structure including zirconia particles 1 containing ZrO2, HfO2, a stabilizer capable of suppressing the phase transition of zirconia, and Nb2O5 and / or Ta2O5, a release component 2 containing a capping element or ion, and, if necessary, an adhesive component 3 containing ZrO2, HfO2, Nb2O5 and / or Ta2O5, and a metal element (e.g., Ti, etc.) derived from the zirconia reinforcement agent. ZrO2, HfO2, Nb2O5 and / or Ta2O5 are each partially present in both the zirconia particles 1 and the adhesive component 3. Furthermore, in the zirconia composite sintered body of the present invention, grain boundaries 4 are also present where no exfoliation components 2 are present, and exfoliation components 2 containing capping elements or ions are present in an appropriate amount at the grain boundaries. It is therefore presumed that this allows the grain boundary strength to be appropriately reduced while minimizing the reduction in strength. A schematic diagram of an estimated structure of a zirconia composite sintered body according to an embodiment containing a zirconia reinforcement is shown in Fig. 1. Even when the adhesive component 3 of the zirconia composite sintered body containing a zirconia reinforcement is present, the effect of reducing the grain boundary strength obtained by the peeling component 2 is not suppressed, and the strength can be increased.
[0023] The capping element or ion becomes a +1-valent cation or -1-valent anion at the grain boundary of the black zirconia composite sintered body and bonds with the bonds of the zirconia composite oxide. This bond causes electrostatic repulsion between the cations or anions, which weakens the grain boundary strength while maintaining the strength properties of the particles constituting the black zirconia composite sintered body, and acts in the direction of improving machinability. For example, as shown in FIG. 2(a), a +1-valent cation may be bonded to the other bond of an oxygen atom bonded to a metal element (e.g., Zr, Hf, Y, Nb, or Ta) contained in the zirconia-based composite oxide in place of the metal element. + represents a +1 cation. As shown in FIG. 2(b), a −1-valent anion is bonded to a metal element (e.g., Zr, Hf, Y, Nb, or Ta) contained in the zirconia-based composite oxide. 2+ It is possible that the molecule may bind to Furthermore, as shown in FIG. 2(c), a form is considered in which a -1-valent anion is contained in the zirconia-based composite oxide and is bonded to a cation derived from a metal element (e.g., Zr, Hf, Y, Nb, or Ta) that is bonded to another metal element. In FIG. 2(b) and (c), X - represents a -1-valent anion. In FIG. 2, (a) to (c) show schematic diagrams of interactions between charged sites at grain boundaries and adsorption sites.
[0024] In addition, since Nb2O5 and / or Ta2O5 act in the direction of coarsening the microstructure and reducing the hardness in the black zirconia composite sintered body, the capping element or ion and Nb2O5 and / or Ta2O5 act together to improve the machinability. Therefore, the capping element or ion and Nb2O5 and / or Ta2O5 act together to provide excellent machinability while maintaining suitable strength, and in addition to being able to shorten the machining time, it is possible to suppress the wear of the machining tool, and the number of processed bodies obtained by continuous processing using one machining tool can be increased, and it is presumed that the problems specific to continuous processing of zirconia sintered bodies can also be solved.
[0025] In the black zirconia composite sintered body of the present invention, the capping element or ion acts as an agent for imparting machinability as described above, and further does not significantly impair the strength.
[0026] The content of the capping element or ion contained in the black zirconia composite sintered body of the present invention is preferably more than 0 mol% and 5 mol% or less, and from the viewpoint of excellent machinability and enabling a further increase in the number of workpieces that can be continuously machined with one machining tool, the content is more preferably 0.05 mol% or more and 3 mol% or less, even more preferably 0.06 mol% or more and 2.5 mol% or less, particularly preferably 0.07 mol% or more and 1.0 mol% or less, and most preferably 0.08 mol% or more and 0.34 mol% or less. Furthermore, when the capping element or ion contained in the black zirconia composite sintered body of the present invention is a Group 17 element or ion, in order to provide superior machinability and to increase the number of workpieces that can be continuously machined with one machining tool, the capping element or ion is more preferably 0.2 mol% or more and 5 mol% or less, even more preferably 0.3 mol% or more and 4 mol% or less, particularly preferably 0.4 mol% or more and 3.5 mol% or less, and most preferably 0.5 mol% or more and 3.0 mol% or less.
[0027] As described above, it is important that the capping element or ion is a +1-valent cation or a -1-valent anion and is present at the grain boundary in order to exhibit appropriate interaction between the charged sites at the grain boundary and the adsorption sites.
[0028] As the capping element or ion, preferred are elements or ions thereof belonging to the second to seventh periods of the periodic table and having a smaller first ionization energy than the group 18 elements of the same period, elements or ions thereof having high electron affinity, nitrate ions, hypochlorite ions, chlorite ions, chlorate ions, perchlorate ions, bromate ions, permanganate ions, metaborate ions, and cyanide ions. In one preferred embodiment, the black zirconia composite sintered body includes an element or an ion thereof derived from the capping agent, which belongs to Periods 2 to 7 of the periodic table and has a smaller first ionization energy than that of a Group 18 element in the same period, and / or an element or an ion thereof having a high electron affinity.
[0029] Preferred examples of elements belonging to the second to seventh periods of the periodic table and having a smaller first ionization energy than the group 18 elements in the same period include Cu, Ag, Li, Na, K, Rb, Cs, Fr, and the like, because they have an easier time obtaining a +1 valent cation and have excellent machinability.
[0030] As the element having a high electron affinity, the Group 17 elements are preferable because −1-valent anions are more easily obtained and machinability is superior. As the Group 17 elements, At, I, Br, Cl, and F are preferable.
[0031] The first ionization energy is the energy required to remove one electron from a neutral atom and ionize it. The first ionization energy can be the same as the first ionization energy described in "Schreiber-Atkins Inorganic Chemistry (Vol. 1), 4th Edition, Part I, Fundamentals, 1. Atomic Structure". The first ionization energy can be converted to "KJ / mol" units using the unit "eV" of first ionization energy described in "Schreiber-Atkins Inorganic Chemistry (Vol. 1), 4th Edition, Appendix 2" as 1 eV = 96.485 KJ / mol. The first ionization energy can also be determined by photoelectron yield spectroscopy (PYS). Electron affinity (EA) is the energy released when an electron is added to a neutral atom. Electron affinity can be measured by the difference in the energy gap from the ionization potential. The ionization potential is defined as the energy difference between the highest-energy occupied orbital of the compound's molecules and the vacuum level, and its value is measured using ultraviolet photoelectron spectroscopy. As the first ionization energy and electron affinity, data accumulated in the NIST Chemistry WebBook (https: / / webbook.nist.gov / chemistry / ) may be used (select Ionization Energy or Electron Affinity from Ion energetics properties). The first ionization energy and electron affinity are sufficient as long as they can compare the likelihood of an element becoming a +1-valent cation or a -1-valent anion with other comparison elements, and the measurement methods described above can be used as appropriate.
[0032] Specific examples of capping elements include Cu, Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl, and F. Of these, Cu, Ag, Li, Na, K, Rb, Cs, Fr, I, Br, Cl, and F are preferred in terms of further improving machinability. In a preferred embodiment, the element derived from the capping agent includes at least one element selected from the group consisting of Cu, Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl, and F, and the ion of the element is at least one +1-valent cation or -1-valent anion selected from the group consisting of Cu, Ag, Li, Na, K, Rb, Cs, Fr, I, Br, Cl, and F. In another preferred embodiment, the element or ion derived from the capping agent includes at least one element or ion thereof selected from the group consisting of Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl, and F. The capping elements or ions may be used alone or in combination of two or more.
[0033] In the black zirconia composite sintered body of the present invention, the total content of ZrO2 and HfO2 is 78 to 97.5 mol% in a total of 100 mol% of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5. From the viewpoint of superior strength, the total content is preferably 79 mol% or more and 96 mol% or less, more preferably 80 mol% or more and 94 mol% or less, and even more preferably 81 mol% or more and 93 mol% or less. As described above, in the black zirconia composite sintered body of the present invention, Nb2O5 and Ta2O5 act to coarsen the microstructure and reduce the hardness, and act together with the capping elements or ions to impart excellent machinability, so that the black zirconia composite sintered body of the present invention has excellent machinability in the sintered body state, despite the high total content of ZrO2 and HfO2 of 78 to 97.5 mol%.
[0034] Examples of stabilizers capable of suppressing the phase transition of zirconia include calcium oxide (CaO), magnesium oxide (MgO), yttrium oxide (Y2O3), cerium oxide (CeO2), scandium oxide (Sc2O3), lanthanum oxide (La2O3), erbium oxide (Er2O3), praseodymium oxide (Pr2O3, Pr6O 11Examples of the oxide include samarium oxide (Sm2O3), europium oxide (Eu2O3), thulium oxide (Tm2O3), gallium oxide (Ga2O3), indium oxide (In2O3) and ytterbium oxide (Yb2O3), and Y2O3 (yttria) and / or CeO2 are preferred because they provide better effects of the present invention and are particularly aesthetically pleasing. The stabilizers may be used alone or in combination of two or more.
[0035] As described above, the capping element or ion acts together with Nb2O5 and / or Ta2O5, and therefore the effect of the stabilizer is not impaired, and the stabilizer is not particularly limited, and the effects of the present invention are achieved.
[0036] In the black zirconia composite sintered body of the present invention, the content of the stabilizer capable of suppressing the phase transition of zirconia is 1 to 12 mol% in a total of 100 mol% of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5. In order to easily obtain sufficient machinability, the content is preferably 2 mol% or more and 10 mol% or less, and in order to obtain superior strength, the content is more preferably 3 mol% or more and 8 mol% or less, and even more preferably 3.5 mol% or more and 7.5 mol% or less. As a preferred embodiment, there is mentioned a black zirconia composite sintered body in which a stabilizer capable of suppressing a phase transition of zirconia contains Y2O3 and / or CeO2, and the total content of Y2O3 and CeO2 is 2 mol% or more and 10 mol% or less. Another preferred embodiment is a black zirconia composite sintered body in which a stabilizer capable of suppressing a phase transition of zirconia contains Y2O3 and the content of Y2O3 is 2 mol% or more and 10 mol% or less. In any of the above-described embodiments, the content of Y2O3 and CeO2 can be appropriately changed within the range described in this specification. For example, in order to obtain superior strength, the total content of Y2O3 and CeO2 may be 2.5 mol% or more and 10 mol% or less, or 3 mol% or more and 9 mol% or less.
[0037] In the black zirconia composite sintered body of the present invention, the total content of Nb2O5 and Ta2O5 is 1 to 9 mol%, preferably 1.5 mol% to 8.5 mol%, in the total of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5 being 100 mol%, and more preferably 2.5 mol% to 8 mol%, and even more preferably 3 mol% to 7 mol% in terms of acting integrally with the capping element or ion and having better machinability. If the total content of Nb2O5 and Ta2O5 is less than 1 mol%, it is difficult to obtain sufficient machinability. Also, if the total content of Nb2O5 and Ta2O5 exceeds 9 mol%, chipping occurs in the obtained black zirconia composite sintered body, making it difficult to obtain sufficient physical properties.
[0038] As described above, Nb2O5 and Ta2O5 act to coarsen the microstructure and reduce hardness, and act together with the capping elements or ions to impart excellent machinability. In addition, they interact with other components (e.g., TiO2, Al2O3) added to the black zirconia composite sintered compact and, through the application of HIP, maximize the sintered density, making it easier to obtain a black zirconia composite sintered compact with better design properties.
[0039] The content of each of the above-mentioned ZrO2, HfO2, stabilizer, Nb2O5, and Ta2O5 components is the percentage relative to the total of 100 mol% of ZrO2, HfO2, stabilizer, Nb2O5, and Ta2O5, and the total of ZrO2, HfO2, stabilizer, Nb2O5, and Ta2O5 does not exceed 100 mol%. For example, when the raw material composition contains Nb2O5 but does not contain Ta2O5, the content of each of the ZrO2, HfO2, stabilizer, and Nb2O5 components means the content percentage relative to the total of 100 mol% of ZrO2, HfO2, stabilizer, and Nb2O5.
[0040] Furthermore, when the content of the stabilizer is A mol % and the total content of Nb2O5 and Ta2O5 is B mol %, the ratio A / B is preferably 0.9 or more and 3 or less from the viewpoint of machinability, and more preferably 0.95 or more and 2 or less, and even more preferably 1 or more and 1.6 or less, because this enhances the effect of the capping element or ion acting together with Nb2O5 and / or Ta2O5, thereby imparting better machinability, suppressing wear of the machining tool, and further increasing the number of processed bodies obtained by continuous machining using one machining tool.
[0041] A preferred embodiment of the present invention includes ZrO2, HfO2, a stabilizer capable of suppressing a phase transformation of zirconia, and Nb2O5 and / or Ta2O5, In the case where the total amount of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5 is 100 mol%, The total content of ZrO2 and HfO2 is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%, further comprising a capping element or ion, the stabilizer comprises Y2O3 and / or CeO2; The content of the capping element or ion is more than 0 mol% and 3 mol% or less with respect to the total of 100 mol% of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5; When the content of the stabilizer is A mol % and the total content of Nb2O5 and Ta2O5 is B mol %, the black zirconia composite sintered body has an A / B ratio of 0.9 or more and 3 or less.
[0042] An embodiment of the present invention includes a black zirconia composite sintered body comprising, in addition to ZrO2, HfO2, a stabilizer capable of suppressing a phase transformation of zirconia, Nb2O5 and / or Ta2O5, and a capping element or ion, a zirconia toughening agent. The zirconia strengthening agent acts integrally with the capping element or ion in a black zirconia composite sintered body containing ZrO2, HfO2, a stabilizer capable of suppressing the phase transition of zirconia, and Nb2O5 and / or Ta2O5, and can improve the strength of the sintered body.
[0043] As described above, in the black zirconia composite sintered body containing a zirconia reinforcement agent, the total content of ZrO2 and HfO2, the type and content of the stabilizer, the total content of Nb2O5 and Ta2O5, the type and content of the capping element or ion, and the A / B ratio can be appropriately changed.
[0044] In a black zirconia composite sintered body containing a zirconia reinforcing agent, the content of the zirconia reinforcing agent is preferably more than 0 mass% and not more than 5.0 mass%, relative to a total of 100 mass% of ZrO2, HfO2, a stabilizer capable of suppressing a phase transition of zirconia, Nb2O5, and Ta2O5, in order to suppress the effect on the black color, and is more preferably 0.01 mass% or more and 4.5 mass% or less, and even more preferably 0.5 mass% or more and 4.0 mass% or less, in order to act together when combined with a capping element or ion, and to achieve excellent machinability and strength.
[0045] Examples of the zirconia reinforcing agent include TiO2, Al2O3, etc. The zirconia reinforcing agent may be used alone or in combination of two or more kinds.
[0046] As a preferred embodiment, there is mentioned a black zirconia composite sintered body, in which the zirconia reinforcing agent contains TiO2 and the TiO2 content is 0.6 to 3.7 mass %.
[0047] In one preferred embodiment, the composition includes ZrO2, HfO2, a stabilizer capable of suppressing the phase transformation of zirconia, and Nb2O5 and / or Ta2O5, In the case where the total amount of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5 is 100 mol%, The total content of ZrO2 and HfO2 is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%, further comprising a capping element or ion, the stabilizer comprises Y2O3 and / or CeO2; The zirconia reinforcement agent contains TiO2, and the TiO2 content is 0.6 to 3.7 mass%; The content of the capping element or ion is more than 0 mol% and 3 mol% or less with respect to the total of 100 mol% of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5; When the content of the stabilizer is A mol % and the total content of Nb2O5 and Ta2O5 is B mol %, the black zirconia composite sintered body has an A / B ratio of 0.9 or more and 3 or less.
[0048] The average crystal grain size of the black zirconia composite sintered body of the present invention is preferably 0.5 to 5.0 μm, more preferably 0.5 to 4.5 μm, and even more preferably 1.0 to 4.0 μm, from the viewpoint of superior machinability and strength. The method for measuring the average crystal grain size is as described in the Examples below. The average crystal grain size can be measured by adjusting the number of particles so that the number of particles contained in one field of view of an SEM photograph is about 50 or 100, in the method described in the Examples.
[0049] The density of the black zirconia composite sintered body is set at 5.5 g / cm because the higher the density, the fewer the internal voids and the greater the strength. 3 It is preferable that the content is 5.7 g / cm or more. 3 More preferably, it is 5.9 g / cm or more. 3 More preferably, it is equal to or greater than this. It is particularly preferable that the black zirconia composite sintered body contains substantially no voids. The density of the compound sintered body can be calculated by (mass of the compound sintered body) / (volume of the compound sintered body).
[0050] Another embodiment of the present invention is a ceramic ceramic comprising ZrO2, HfO2, a stabilizer capable of inhibiting a phase transformation of zirconia, and Nb2O5 and / or Ta2O5, In the case where the total amount of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5 is 100 mol%, The total content of ZrO2 and HfO2 is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%, producing a molded body using a raw material composition further containing a capping agent; and sintering the green body.
[0051] The raw material composition used for producing the black zirconia composite sintered body includes ZrO2, HfO2, a stabilizer capable of suppressing the phase transition of zirconia, Nb2O5 and / or Ta2O5, and a capping agent. The raw material composition for the black zirconia composite sintered body may be in a dry state, or may be in a state containing a liquid or in a state contained in a liquid. The raw material composition may be in the form of, for example, a powder, granules or granulated material, a paste, a slurry, or the like.
[0052] The raw material composition contains a capping agent so that the resulting black zirconia composite sintered body contains a capping element or ion. The capping agent is not particularly limited as long as it is a compound that can become a monovalent ion (a +1-valent cation or a -1-valent anion) in a solvent containing water, and examples thereof include hydroxides, salts, halides (fluorides, chlorides, bromides, iodides), cyanides, etc., that contain an element or ion derived from the capping agent. Each of the capping agents may be used alone or in combination of two or more.
[0053] Examples of hydroxides containing capping elements or ions include lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, francium hydroxide, and the like. Salts containing capping elements or ions include, for example, carbonates, bicarbonates, nitrates, hypochlorites, chlorites, chlorates, perchlorates, bromates, permanganates, metaborates, sulfide salts, and cyanide salts.
[0054] Carbonates containing capping elements or ions include, for example, lithium carbonate, sodium carbonate, potassium carbonate, rubidium carbonate, francium carbonate, cesium carbonate, and the like. Examples of hydrogen carbonates containing a capping element or ion include lithium hydrogen carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, rubidium hydrogen carbonate, francium hydrogen carbonate, and cesium hydrogen carbonate. Examples of nitrates containing capping elements or ions include calcium nitrate, strontium nitrate, iron(II) nitrate, iron(III) nitrate, cobalt(II) nitrate, magnesium nitrate, gallium nitrate, yttrium(III) nitrate, lanthanum(III) nitrate, praseodymium nitrate, neodymium(III) nitrate, manganese(II) nitrate, europium nitrate, copper(II) nitrate, thorium nitrate, aluminum nitrate, nickel(II) nitrate, chromium(III) nitrate, titanium(IV) nitrate, zirconium oxynitrate(IV) hydrate (ZrO(NO3)2·xH2O), cerium(III) nitrate, tin nitrate, bismuth(III) nitrate, scandium(III) nitrate, indium(III) nitrate, and hafnium(IV) nitrate. Hypochlorites containing capping elements or ions include, for example, sodium hypochlorite, calcium hypochlorite, and the like. Examples of chlorites containing a capping element or ion include sodium chlorite, potassium chlorite, lithium chlorite, calcium chlorite, magnesium chlorite, barium chlorite, copper(II) chlorite, copper(III) chlorite, silver chlorite, nickel chlorite, and the like. Chlorates containing capping elements or ions include, for example, calcium chlorate, barium chlorate, cobalt chlorate, nickel chlorate, magnesium chlorate, zinc chlorate, copper chlorate, and the like. Perchlorates containing capping elements or ions include, for example, iron (III) perchlorate, barium perchlorate, calcium perchlorate, cobalt perchlorate, nickel perchlorate, magnesium perchlorate, beryllium perchlorate, aluminum perchlorate, and cerium perchlorate. Bromates containing capping elements or ions include, for example, neodymium bromate, lanthanum bromate, praseodymium bromate, and the like. Permanganates containing capping elements or ions include, for example, calcium (VII) permanganate, potassium (VII) permanganate, sodium (VII) permanganate, and the like. Metaborates containing capping elements or ions include, for example, sodium metaborate, barium metaborate, and the like. Sulfide salts containing capping elements or ions include, for example, copper(I) sulfide. Cyanide salts containing capping elements or ions include, for example, barium cyanide, sodium cyanide, potassium cyanide, calcium cyanide, and the like.
[0055] Examples of fluorides containing capping elements or ions include lithium fluoride, sodium fluoride, potassium fluoride, rubidium fluoride, cesium fluoride, francium fluoride, beryllium fluoride, magnesium fluoride, calcium fluoride, strontium fluoride, barium fluoride, scandium (III) fluoride, yttrium (III) fluoride, lanthanum (III) fluoride, cerium (III) fluoride, neodymium (I) fluoride, and fluoride containing ions such as fluoride, ... II), titanium fluoride (III), titanium fluoride (IV), zirconium fluoride (IV), hafnium fluoride (IV), tantalum fluoride (V), manganese fluoride (II), manganese fluoride (III), iron fluoride (II), iron fluoride (III), copper fluoride (II), zinc fluoride (II), aluminum fluoride, chromium fluoride (III), bismuth fluoride (III), indium fluoride (III), tin fluoride (II), and the like.
[0056] Examples of chlorides containing capping elements or ions include zirconium oxychloride, lithium chloride, sodium chloride, potassium chloride, rubidium chloride, cesium chloride, francium chloride, beryllium chloride, magnesium chloride, calcium chloride, strontium chloride, barium chloride, scandium chloride (III), yttrium chloride (III), lanthanum chloride (III), cerium chloride (III), praseodymium chloride, neodymium chloride (III), samarium chloride, europium chloride, titanium chloride (III), titanium chloride (IV), zirconium chloride (IV), hafnium chloride (IV), tantalum chloride (V), manganese chloride, iron chloride (II), iron chloride (III), cobalt chloride (II), nickel chloride (II), copper chloride (I), copper chloride (II), zinc chloride (II), aluminum chloride, gallium chloride, bismuth chloride (III), indium chloride (I), indium chloride (III), and tin chloride (II).
[0057] Examples of bromides containing capping elements or ions include lithium bromide, sodium bromide, potassium bromide, rubidium bromide, cesium bromide, francium bromide, beryllium bromide, magnesium bromide, calcium bromide, strontium bromide, barium bromide, scandium (III) bromide, yttrium (III) bromide, cerium (III) bromide, neodymium (III) bromide, titanium (IV) bromide, zirconium (IV) bromide, tantalum (V) bromide, manganese (II) bromide, iron (II) bromide, iron (III) bromide, cobalt (II) bromide, nickel (II) bromide, copper (I) bromide, copper (II) bromide, zinc (II) bromide, chromium (III) bromide, bismuth (III) bromide, vanadium (III) bromide, indium (III) bromide, and tin bromide.
[0058] Examples of iodides containing capping elements or ions include lithium iodide, sodium iodide, potassium iodide, rubidium iodide, cesium iodide, francium iodide, beryllium iodide, calcium iodide, magnesium iodide, strontium iodide, barium iodide, scandium (III) iodide, yttrium (III) iodide, lanthanum (III) iodide, cerium (III) iodide, neodymium (III) iodide, titanium (IV) iodide, ), zirconium iodide (IV), hafnium iodide (IV), tantalum iodide (V), manganese iodide (II), iron iodide (II), iron (III), cobalt iodide (II), nickel iodide (II), copper iodide (I), zinc iodide (II), aluminum iodide, chromium iodide (III), vanadium iodide (II), bismuth iodide (III), indium iodide (III), tin iodide (II), and tin iodide (IV).
[0059] For ZrO2 and HfO2, commercially available zirconia powder can be used. Examples of commercially available products include zirconia powder (trade name "Zpex (registered trademark)" (Y2O3 content: 3 mol%), "Zpex (registered trademark) 4" (Y2O3 content: 4 mol%), "Zpex (registered trademark) 4" (Y2O3 content: 4 mol%), Smile (registered trademark) (Y2O3 content: 5.5 mol%), TZ-3Y (Y2O3 content: 3 mol%), TZ-3YS (Y2O3 content: 3 mol%), TZ-4YS (Y2O3 content: 4 mol%), TZ-6Y (Y2O3 content: 6 mol%), TZ-6YS (Y2O3 content: 6 mol%), TZ-8YS (Y2O3 content: 8 mol%), TZ-10YS (Y2O3 content: 10 mol%), TZ-3Y-E (Y2O3 content: 3 mol%) "TZ-3YS-E" (Y2O3 content: 3 mol%), "TZ-3YB-E" (Y2O3 content: 3 mol%), "TZ-3YSB-E" (Y2O3 content: 3 mol%), "TZ-3YB" (Y2O3 content: 3 mol%), "TZ-3YSB" (Y2O3 content: 3 mol%), "TZ-3Y20AB" (Y2O3 content: 3 mol%), "TZ-8YSB" (Y2O3 content: 8 mol%), "TZ-0" (Y2O3 content: 0 mol%); all manufactured by Tosoh Corporation. The commercially available zirconia powder also contains HfO2. Commercially available products that also contain Y2O3 can also be used. As the zirconia powder, the raw material composition of the present invention can also use zirconia powder in which Y2O3 is uniformly dispersed and solid-solved, such as the commercially available TZ series (part of the product name includes "TZ").
[0060] There are no particular limitations on the method for producing the zirconia powder, and any known method can be used, such as a breakdown process in which coarse particles are pulverized into fine powder, or a building-up process in which zirconia powder is synthesized from atoms or ions through a nucleation and growth process.
[0061] The type of zirconia powder in the raw material composition is not particularly limited, and when the zirconia powder contains ZrO2 and HfO2 and does not contain a stabilizer, or when the content of the stabilizer is increased as necessary, stabilizer particles can be added separately. The stabilizer particles are not particularly limited as long as the content of the stabilizer contained in the black zirconia composite sintered body can be adjusted to the above-mentioned predetermined range. The particles of the stabilizer may be, for example, a commercially available product, or a powder of the commercially available product may be ground in a known grinding and mixing device (such as a ball mill) before use.
[0062] The stabilizer may be either one that is not solid-dissolved in ZrO2 and HfO2 or one that is solid-dissolved in ZrO2 and HfO2. In a preferred embodiment, the method for producing a black zirconia composite sintered body includes a stabilizer (preferably, Y2O3) that is not solid-dissolved in ZrO2 and HfO2, because this is one factor that makes it easy to obtain the desired black zirconia composite sintered body in the raw material composition. The fact that the stabilizer includes one that is not solid-dissolved in zirconia can be confirmed, for example, by an X-ray diffraction (XRD) pattern.
[0063] When a peak attributable to the stabilizer is confirmed in the XRD pattern of the raw material composition or the molded body, it means that the stabilizer is present in the raw material composition or the molded body without being dissolved in ZrO2 and HfO2. When the entire amount of the stabilizer is dissolved in ZrO2 and HfO2, basically, no peaks derived from the stabilizer are observed in the XRD pattern. However, depending on the conditions such as the crystal state of the stabilizer, even if there is no stabilizer peak in the XRD pattern, the stabilizer may not be dissolved in ZrO2 and HfO2.
[0064] The case where the stabilizer includes a stabilizer that is not solid-dissolved in ZrO2 and HfO2 will be described below by taking an example in which the stabilizer is yttria.
[0065] In the raw material composition or molded body of the present invention, the abundance rate f of yttria that is not dissolved in ZrO2 and HfO2 (hereinafter sometimes referred to as "undissolved yttria") is y can be calculated based on the following formula (1). f y =I 29 / (I 28 +I 29 +I 30 ) x 100 (In the formula, f y represents the percentage of undissolved yttria (%). In the XRD measurement, I 28 represents the integrated intensity of the peak at 2θ = 28° where the main monoclinic peak appears, and I 29 represents the intensity of the peak at 2θ = 29° where the main peak of yttria appears, and I 30 represents the integrated intensity of the peak near 2θ=30° where the main peak of the tetragonal or cubic crystal system appears.)
[0066] In addition, when a stabilizer other than yttria is used, I 29 By substituting the peak of another stabilizer instead of yttria, the above formula can also be applied to calculate the undissolved fraction of stabilizers other than yttria.
[0067] Undissolved yttria abundance f y From the viewpoint of facilitating the production of the desired black zirconia composite sintered body, the content of undissolved yttria f is preferably greater than 0%, more preferably 1% or more, even more preferably 2% or more, and particularly preferably 3% or more. y The upper limit may be, for example, 25% or less, but preferably depends on the content of yttria in the raw material composition or the molded body.
[0068] For example, when the content of yttria in the raw material composition or molded article of the present invention is 3 mol % or more and 8 mol % or less, the following applies. When the yttria content is 3 mol% or more and less than 4.5 mol%, f yWhen the yttria content is 4.5 mol% or more and less than 5.8 mol%, f y When the yttria content is 5.8 mol% or more and 8 mol% or less, f y may be no more than 25%.
[0069] For example, when the yttria content is 3 mol% or more and less than 4.5 mol%, f y is preferably 2% or more, more preferably 3% or more, even more preferably 4% or more, and particularly preferably 5% or more. When the yttria content is 4.5 mol% or more and less than 5.8 mol%, f y is preferably 3% or more, more preferably 4% or more, even more preferably 5% or more, even more preferably 6% or more, and particularly preferably 7% or more. When the yttria content is 5.8 mol% or more and 8 mol% or less, f y is preferably 4% or more, more preferably 5% or more, even more preferably 6% or more, even more preferably 7% or more, and particularly preferably 8% or more.
[0070] In the raw material composition or molded body of the present invention, the entire stabilizer does not have to be solid-dissolved in ZrO2 and HfO2. In the present invention, the stabilizer being solid-dissolved means, for example, that an element (atom) contained in the stabilizer is solid-dissolved in ZrO2 and HfO2.
[0071] The Nb2O5 and / or Ta2O5 added to the raw material composition of the present invention is not particularly limited as long as the content of Nb2O5 and / or Ta2O5 contained in the black zirconia composite sintered body can be adjusted to the above-mentioned predetermined range. Nb2O5 and / or Ta2O5 are not particularly limited, and for example, commercially available products may be used, or the commercially available powder may be crushed with a known crushing and mixing device (such as a ball mill) before use.
[0072] Examples of the process for preparing the raw material composition include a method in which the raw materials of the raw material composition (ZrO2, HfO2, a stabilizer, Nb2O5 and / or Ta2O5, a capping agent (e.g., a compound that can become a monovalent ion in a solvent containing water), and optionally a zirconia reinforcing agent) are wet-mixed in a solvent containing water to obtain the raw material composition.
[0073] The method for wet-mixing the raw materials in a solvent containing water is not particularly limited. For example, the raw materials may be wet-pulverized and mixed in a known pulverizing and mixing device (such as a ball mill) to form a slurry, and then the slurry may be dried and granulated to produce a granular raw material composition.
[0074] In the wet mixing step, additives such as a binder, a plasticizer, a dispersant, an emulsifier, an antifoaming agent, a pH adjuster, a lubricant, etc. may be further included. Each of the additives may be used alone or in combination of two or more kinds.
[0075] The binder may be added to the milled slurry after a primary powder of a mixture of ZrO2, HfO2, Y2O3, Nb2O5 and / or Ta2O5, and a capping agent is added to water to form a slurry.
[0076] The binder is not particularly limited, and known binders can be used. Examples of binders include polyvinyl alcohol binders, acrylic binders, wax binders (paraffin wax, etc.), methyl cellulose, carboxymethyl cellulose, polyvinyl butyral, polymethyl methacrylate, ethyl cellulose, polyethylene, polypropylene, ethylene-vinyl acetate copolymers, polystyrene, atactic polypropylene, and methacrylic resins.
[0077] Examples of the plasticizer include polyethylene glycol, glycerin, propylene glycol, and dibutyl phthalate.
[0078] Examples of dispersants include ammonium polycarboxylate (e.g., triammonium citrate), ammonium polyacrylate, acrylic copolymer resin, acrylic acid ester copolymer, polyacrylic acid, bentonite, carboxymethyl cellulose, anionic surfactants (e.g., polyoxyethylene alkyl ether phosphates such as polyoxyethylene lauryl ether phosphate), nonionic surfactants, olein glyceride, amine salt surfactants, oligosaccharide alcohols, and stearic acid.
[0079] Examples of the emulsifier include alkyl ethers, phenyl ethers, and sorbitan derivatives.
[0080] Examples of the defoaming agent include alcohol, polyether, silicone, wax, and the like.
[0081] Examples of pH adjusters include ammonia, ammonium salts (including ammonium hydroxides such as tetramethylammonium hydroxide), and the like.
[0082] Examples of the lubricant include polyoxyethylene alkyl ether and wax.
[0083] The solvent used in the wet mixing is not particularly limited as long as it contains water, and an organic solvent may be used, a mixed solvent of water and an organic solvent may be used, or only water may be used. Examples of the organic solvent include ketone solvents such as acetone and ethyl methyl ketone; and alcohol solvents such as ethanol, 1-propanol, 2-propanol, 2-methyl-2-propanol, glycerin, diglycerin, polyglycerin, propylene glycol, dipropylene glycol, polypropylene glycol, ethylene glycol, diethylene glycol, polyethylene glycol, polyethylene glycol monomethyl ether, 1,2-pentanediol, 1,2-hexanediol, and 1,2-octanediol.
[0084] The raw material composition of the black zirconia composite sintered body used in the present invention may contain ZrO2, Y2O3, Nb2O5, Ta2O5, a capping agent, and, if necessary, other components other than the zirconia reinforcement agent, as long as the effects of the present invention are achieved. Examples of the other components include colorants (pigments and composite pigments), fluorescent agents, SiO2, etc. Each of the other components may be used alone or in combination of two or more.
[0085] Examples of the pigment include oxides of at least one element selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd, Tb, and Er (specifically, NiO, Cr2O3, etc.), and oxides of at least one element selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd, and Tb are preferred, and oxides of at least one element selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Sm, Eu, Gd, and Tb are more preferred. However, Y2O3 and CeO2 may be excluded from the pigment.
[0086] Examples of the composite pigment include (Zr,V)O2, Fe(Fe,Cr)2O4, (Ni,Co,Fe)(Fe,Cr)2O4·ZrSiO4, and (Co,Zn)Al2O4.
[0087] Examples of the fluorescent agent include Y2SiO5:Ce, Y2SiO5:Tb, (Y,Gd,Eu)BO3, Y2O3:Eu, YAG:Ce, ZnGa2O4:Zn, and BaMgAl 10 O 17 :Eu, etc.
[0088] Next, the obtained raw material composition is molded to produce a molded body. The molding method is not particularly limited, and a known method (for example, press molding, etc.) can be used.
[0089] In the case of producing a zirconia molded body by a method having a step of press-molding a raw material composition, the specific method of press molding is not particularly limited, and can be performed using a known press molding machine. Specific examples of the press molding method include uniaxial pressing.
[0090] The pressing pressure is set to an appropriate optimum value depending on the size, open porosity, biaxial bending strength, and particle size of the raw material powder of the target molded body, and is usually 5 MPa to 1000 MPa. By increasing the pressing pressure during molding in the above-mentioned manufacturing method, the pores of the obtained molded body are filled more, the open porosity can be set low, and the density of the molded body can be increased. In addition, in order to increase the density of the obtained zirconia molded body, a cold isostatic pressing (CIP) treatment may be further performed after uniaxial pressing.
[0091] Next, the resulting green body is sintered. The term "molded body" refers to a body that has not yet reached a semi-sintered state (calcined state) or a sintered state. In other words, the molded body is distinguished from the calcined body and the sintered body in that the molded body is a body that has been molded and then not sintered. The sintering temperature (maximum sintering temperature) for obtaining the black zirconia composite sintered body is, for example, preferably 1300°C or higher, more preferably 1350°C or higher, even more preferably 1400°C or higher, even more preferably 1450°C or higher, and particularly preferably 1500°C or higher. The sintering temperature is, for example, preferably 1680°C or lower, more preferably 1650°C or lower, and even more preferably 1600°C or lower. In the method for producing the black zirconia composite sintered body of the present invention, it is preferable to sinter the molded body at a maximum sintering temperature of 1400 to 1680°C. The maximum sintering temperature is preferably a temperature in the atmosphere.
[0092] The holding time (holding time) at the maximum sintering temperature depends on the temperature, but is preferably 30 hours or less, more preferably 20 hours or less, even more preferably 10 hours or less, even more preferably 5 hours or less, particularly preferably 3 hours or less, and most preferably 2 hours or less. Furthermore, the holding time can be 25 minutes or less, 20 minutes or less, or 15 minutes or less. Moreover, the holding time is preferably 1 minute or more, more preferably 5 minutes or more, and even more preferably 10 minutes or more. According to the manufacturing method of the present invention, a black zirconia composite sintered body excellent in bending strength and machinability can be produced depending on the content of the stabilizer. Moreover, the sintering time may be shortened as long as the effect of the present invention can be obtained. By shortening the sintering time, it is possible to increase production efficiency and reduce energy costs.
[0093] In the method for producing a black zirconia composite sintered body of the present invention, when the molded body is sintered, the heating rate is not particularly limited, and is preferably 0.1° C. / min or more, more preferably 0.2° C. / min or more, and even more preferably 0.5° C. / min or more. The heating rate is preferably 50° C. / min or less, more preferably 30° C. / min or less, and even more preferably 20° C. / min or less. When the heating rate is equal to or more than the lower limit, productivity is improved.
[0094] A general zirconia firing furnace can be used in the step of sintering the molded body. Commercially available zirconia firing furnaces may be used. Examples of commercially available zirconia firing furnaces include Noritake Katana (registered trademark) F-1, F-1N, and F-2 (all manufactured by SK Medical Electronics Co., Ltd.).
[0095] In the method for producing a black zirconia composite sintered body, a black zirconia composite sintered body can also be obtained by sintering a green body to which a black pigment has been added. Examples of black pigments include black organic pigments, mixed color organic pigments, and inorganic pigments. Examples of black organic pigments include carbon black, perylene black, aniline black, benzofuranone pigments, etc. These may be coated with a resin. The mixed color organic pigments include, for example, pigments obtained by mixing two or more kinds of pigments such as red, blue, green, purple, yellow, magenta, and / or cyan to produce a pseudo-black color. Examples of black inorganic pigments include graphite; fine particles of metals such as titanium, copper, iron, manganese, cobalt, chromium, nickel, zinc, calcium, and silver; metal oxides; metal composite oxides; metal sulfides; metal nitrides; metal oxynitrides; and metal carbides. However, when a pigment containing titanium is used as the black pigment, it is preferable that the total titanium content does not exceed 5.0 mass %, which is the upper limit of the TiO2 content of the zirconia reinforcing agent.
[0096] In addition to or instead of the method of adding a black pigment to the green body, it is preferable to subject the green body to reduction firing in addition to sintering at the above-mentioned maximum sintering temperature. In one preferred embodiment, the step of sintering the compact includes a step of reducing and firing the compact in addition to the sintering at the maximum sintering temperature.
[0097] The reduction firing step is not particularly limited as long as it is sintered under a reducing atmosphere, but for example, a step of hot isostatic pressing (HIP) treatment in a reducing atmosphere can be mentioned. By the HIP treatment under a reducing atmosphere, blackening occurs due to oxygen defects, and a black zirconia compound sintered body can be obtained. In addition, the strength of the black zirconia compound sintered body can be further improved by the HIP treatment.
[0098] Hereinafter, the sintered body obtained by sintering at the above-mentioned maximum sintering temperature is referred to as a "primary sintered body", and the sintered body after the HIP treatment is referred to as a "HIP-treated sintered body".
[0099] The HIP treatment can be carried out using a known hot isostatic press (HIP) device.
[0100] The temperature of the HIP treatment is not particularly limited, but since a dense black zirconia composite sintered body with high strength can be obtained, the HIP temperature is preferably 1200° C. or higher, more preferably 1300° C. or higher, and even more preferably 1400° C. or higher. The HIP temperature is preferably 1700° C. or lower, more preferably 1650° C. or lower, and even more preferably 1600° C. or lower.
[0101] In the method for producing the black zirconia composite sintered body of the present invention, when the primary sintered body is subjected to HIP treatment, the HIP pressure is not particularly limited, and since a dense sintered body with high strength can be obtained, the HIP pressure is preferably 100 MPa or more, more preferably 125 MPa or more, and even more preferably 130 MPa or more. The upper limit of the HIP pressure is not particularly limited, but can be, for example, 400 MPa or less, 300 MPa or less, or even 200 MPa or less.
[0102] In the method for producing the black zirconia composite sintered body of the present invention, when the primary sintered body is subjected to HIP treatment, the heating rate is not particularly limited, and is preferably 0.1° C. / min or more, more preferably 0.2° C. / min or more, and even more preferably 0.5° C. / min or more. The heating rate is preferably 50° C. / min or less, more preferably 30° C. / min or less, and even more preferably 20° C. / min or less. The heating rate is equal to or higher than the lower limit, thereby improving productivity.
[0103] In the method for producing the black zirconia composite sintered body of the present invention, when the primary sintered body is subjected to the HIP treatment, the HIP time is not particularly limited, and since a dense black zirconia composite sintered body having high strength can be obtained, the HIP treatment time is preferably 5 minutes or more, more preferably 10 minutes or more, and even more preferably 30 minutes or more. Also, the HIP treatment time is preferably 10 hours or less, more preferably 6 hours or less, and even more preferably 3 hours or less.
[0104] In the method for producing a black zirconia composite sintered body of the present invention, when the primary sintered body is subjected to HIP treatment in a reducing atmosphere, the pressure medium is not particularly limited, and from the viewpoint of having little effect on zirconia, the pressure medium can be at least one selected from the group consisting of inert gases (e.g., nitrogen, argon, etc.).
[0105] In the step of performing the reducing and sintering, it is preferable to perform the reducing and sintering in the presence of carbon, since this increases the efficiency of the sintering in a reducing atmosphere, reduces the L* value of the composite sintered body, and produces a black zirconia composite sintered body with a deeper color. The carbon used in the reduction and firing step is not particularly limited, and examples thereof include Referthermo (a common thermal history sensor, containing a small amount of organic components (organic binder (PVA / PEG type))).
[0106] The black zirconia composite sintered body of the present invention is not particularly limited as long as it exhibits the effects of the present invention, and may be a primary sintered body or a HIP-treated sintered body.
[0107] Although the black zirconia composite sintered body of the present invention is a sintered body, it has excellent machinability, so there is no need to machine the semi-sintered calcined body in the form of a mill blank and then sinter it to form a sintered body. On the other hand, the method for producing the black zirconia composite sintered body may also be a method in which a molded body obtained by using the raw material composition is calcined to produce a calcined body in a semi-sintered state, and the unprocessed calcined body is mechanically processed to produce a sintered body.
[0108] In another embodiment, the method includes the steps of: preparing a molded body using the raw material composition; calcining the obtained molded body to obtain a calcined zirconia body (calcination step); and sintering the calcined zirconia body. A method for producing a black zirconia composite sintered body can be mentioned.
[0109] In order to ensure blocking, the firing temperature (calcination temperature) in the calcination step is, for example, preferably 800° C. or higher, more preferably 900° C. or higher, and even more preferably 950° C. or higher. The calcination temperature is, for example, preferably 1200° C. or lower, more preferably 1150° C. or lower, and even more preferably 1100° C. or lower. The calcination temperature is, for example, preferably 800° C. to 1200° C. At such a calcination temperature, it is considered that the dissolution of the stabilizer does not progress significantly in the calcination step.
[0110] The zirconia calcined body of the present invention means a body in which ZrO2 particles are necked (adhered) to each other and the ZrO2 particles (powder) are in a state where they are not completely sintered (semi-sintered state).
[0111] The density of the calcined zirconia body is 2.7 g / cm 3 The density of the calcined zirconia body is preferably 4.0 g / cm 3 Less than 3.8 g / cm is preferred. 3 Less than 3.6 g / cm is more preferable. 3 The following is even more preferable. When the density is within this range, processing can be easily performed. The density of the calcined body can be calculated, for example, by dividing the mass of the calcined body by the volume of the calcined body.
[0112] The three-point bending strength of the zirconia calcined body is preferably from 15 to 70 MPa, more preferably from 18 to 60 MPa, and even more preferably from 20 to 50 MPa. The bending strength can be measured using a test piece having a thickness of 5 mm, a width of 10 mm, and a length of 50 mm, in accordance with ISO 6872:2015, except for the size of the test piece. The face of the test piece and the C face (the face of the test piece with the corners chamfered at an angle of 45°) are surface-finished in the longitudinal direction with 600-grit sandpaper. The test piece is arranged so that the widest face faces vertically (load direction). In the bending test measurement, the span is 30 mm, and the crosshead speed is 1.0 mm / min.
[0113] The step of sintering the zirconia calcined body can be carried out by the same method and under the same conditions (temperature, pressure, etc.) as the step of sintering the molded body described above. Therefore, in the embodiment of the production method using the zirconia calcined body, the "molded body" can be read as the "calcined body".
[0114] The black zirconia composite sintered body of the present invention has excellent strength. The biaxial bending strength of the black zirconia composite sintered body of the present invention is preferably 300 MPa or more, more preferably 350 MPa or more, even more preferably 400 MPa or more, even more preferably 450 MPa or more, and particularly preferably 500 MPa or more. When the black zirconia composite sintered body of the present invention has such a biaxial bending strength, for example, breakage can be suppressed. There is no particular limit to the upper limit of the biaxial bending strength, but the biaxial bending strength can be, for example, 1200 MPa or less, or even 1000 MPa or less. The biaxial bending strength of the black zirconia composite sintered body can be measured in accordance with ISO 6872:2015.
[0115] The black zirconia composite sintered body of the present invention preferably has a desired color tone in terms of excellent design. The color tone can be evaluated by L*, |a*|, and |b*|. L*, |a*| and |b*| can be calculated by measuring L*, a* and b* according to the L*a*b* color system (JIS Z 8781-4:2013 Colorimetry-Part 4: CIE 1976 L*a*b* color space) on a measurement sample with a diameter of 15 mm and a thickness of 1.2 mm, and then using, for example, a spectrophotometer "CM-3610A" manufactured by Konica Minolta, Inc. under conditions of a D65 light source, measurement mode SCI, and measurement diameter / illumination diameter = φ8mm / φ11mm.
[0116] Regarding color tone, specifically, in the black zirconia composite sintered body of the present invention, when a sample having a diameter of 15 mm and a thickness of 1.2 mm is placed against a white background (underlay) (the side of the sample opposite to the color tone measuring device is placed in white), L* is preferably 60 or less, more preferably 55 or less, and even more preferably 50 or less. In addition, in the above-mentioned samples and measurement conditions, |a*| is preferably 3 or less, more preferably 2 or less, and even more preferably 1 or less. Furthermore, in the above-mentioned sample and measurement conditions, |b*| is preferably 3 or less, more preferably 2.5 or less, and even more preferably 2 or less. As a preferred embodiment, there can be mentioned a black zirconia composite sintered body in which, under the above-mentioned sample and measurement conditions, L* is 60 or less, |a*| is 3 or less, and |b*| is 3 or less. Another preferred embodiment is a black zirconia composite sintered body in which, under the above-mentioned sample and measurement conditions, L* is 50 or less, |a*| is 1 or less, and |b*| is 2 or less. When the L*, |a*|, and |b*| are within the above ranges, a black zirconia composite sintered body having excellent design properties can be obtained.
[0117] One preferred embodiment, from the viewpoint of easily obtaining superior design properties, is a black zirconia composite sintered body in which the colorimetric values measured on a sample having a diameter of 15 mm and a thickness of 1.2 mm against a white background using the L*a*b* color system are L*≦60, |a*|≦3, and |b*|≦3.
[0118] In view of excellent designability, the black zirconia composite sintered body of the present invention has a color tone in which a sample having a diameter of 15 mm and a thickness of 1.2 mm is used to measure the color of the sample against a white background according to the L*a*b* color system. The color saturation C* calculated from a* and b* is preferably 10 or less, more preferably 8 or less, and even more preferably 6 or less. C* is a* obtained by the above method, and b * The average value of chroma C * =((a * ) 2 +(b * ) 2 ) 1 / 2 can be calculated.
[0119] The coefficient of thermal expansion (CTE) of the black zirconia composite sintered body of the present invention is 8×10 -6 / ℃~13×10 -6 / °C, and preferably 8.5×10 -6 / ℃~12×10 -6 / °C, more preferably 9×10 -6 / ℃~11×10 -6 / °C. is even more preferred. Since the black zirconia composite sintered body of the present invention has a coefficient of thermal expansion (CTE) within the above range, it can be suitably used in combination with metal materials. The coefficient of thermal expansion (CTE) can be measured in accordance with ISO 6872:2015, with the analysis temperature range being 25° C. to 500° C., and the measurement can be performed at a heating rate of, for example, 5° C. / min.
[0120] Furthermore, the black zirconia composite sintered body of the present invention is particularly suitable for use in zirconia members that require a special or complicated shape and strength. Compared with sintered bodies manufactured only by existing manufacturing methods (injection molding, CIP, slip casting, 3D printing, etc.), the black zirconia composite sintered body of the present invention can be processed as it is. Therefore, for example, it is economical when a desired zirconia part can be obtained in a short time, and in the case of a complex-shaped part that is difficult to manufacture by conventional manufacturing methods, it is possible to obtain a zirconia part that maintains high strength because there is no need to obtain multiple parts by mechanical fitting. Furthermore, since the sintered body can be processed as it is, a sintering process is not required when dimensional accuracy is required, and since there is no uneven firing shrinkage, a zirconia part can be obtained with high accuracy. In addition, machining can be performed using, for example, a commercially available machining device.
[0121] Specific applications of the black zirconia composite sintered body of the present invention include jewelry applications (brooches, tie pins, handbag fittings, bracelets, etc.), engine parts and interior parts for mobility such as aircraft and automobiles, display panel frames, building parts, portable device parts, luxury daily use parts, watch parts (watch bands, bezels, dials, watch cases, etc.), exterior parts such as housings for portable electronic devices (e.g., smartphones), lighter cases, cosmetic cases, mobile phone cases, and earphone housings, electrical appliance parts, household product parts, logo marks for various products, and toy parts. The zirconia member may also be fitted with a different material to be used as a composite member.
[0122] The present invention includes embodiments in which all or part of the above configurations are combined in various ways within the scope of the technical idea of the present invention, as long as the effects of the present invention are achieved. EXAMPLES
[0123] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples, and many modifications within the scope of the technical concept of the present invention are possible by those having ordinary skill in the art. In the following examples and comparative examples, the average particle size refers to the average primary particle size, which can be determined by a laser diffraction scattering method. Specifically, it can be measured on a volume basis using a laser diffraction particle size distribution measuring device (SALD-2300: manufactured by Shimadzu Corporation) with a 0.2% aqueous solution of sodium hexametaphosphate as a dispersion medium.
[0124] [Examples 1 to 17 and Comparative Examples 1 to 4] The measurement samples of each of the Examples and Comparative Examples were prepared through the steps of preparing a granular raw material composition, preparing a compact, and preparing a sintered body (preparation of a primary sintered body, and HIP treatment).
[0125] [Preparation of granular raw material composition] In order to prepare the granular raw material composition of each Example and Comparative Example, commercially available ZrO2 powder, Y2O3 powder, Nb2O5 powder, Ta2O5 powder, and capping agent, and further zirconia reinforcement powder (TiO2 powder and / or Al2O3 powder) were mixed to the composition shown in Tables 1 and 2, water was added to prepare a slurry, and the mixture was wet-pulverized and mixed in a ball mill until the average particle diameter was 0.13 μm or less. After adding a binder to the pulverized slurry, the mixture was dried with a spray dryer to prepare a granular raw material composition (hereinafter, also simply referred to as "raw material composition"), which was used in the manufacture of a molded body described below. The average particle diameter was measured on a volume basis using a laser diffraction particle size distribution measuring device (SALD-2300: manufactured by Shimadzu Corporation) using a 0.2% sodium hexametaphosphate aqueous solution as a dispersion medium. In Example 17, TZ-3Y (Y2O3 content: 3 mol%):TZ-6Y (Y2O3 content: 6 mol%) were mixed in a ratio of 18.7:81.3, and the ratio of each component was adjusted to the blending ratio shown in Table 1.
[0126] [Preparation of molded body] For each of the Examples and Comparative Examples, pellet-shaped compacts and block-shaped compacts were prepared as follows so as to obtain sintered body samples for evaluating strength and workability. For the pellet-shaped compact, a cylindrical mold having a diameter of 19 mm was used, and the raw material composition was placed in the mold so that the thickness of the black zirconia composite sintered body after sintering would be 1.2 mm. Next, the raw material composition was press-molded at a surface pressure of 200 MPa using a uniaxial press molding machine to produce a pellet-shaped compact.
[0127] For the block-shaped compact, the raw material composition was placed in a metal mold having an inner dimension of 19 mm×18 mm so that the height of the black zirconia composite sintered body after sintering would be 14.5 mm. Next, the raw material composition was press-molded at a surface pressure of 200 MPa using a uniaxial press molding machine to produce a block-shaped compact.
[0128] [Preparation of primary sintered body] The pellet-shaped and block-shaped compacts obtained were subjected to a firing furnace "Noritake Katana (registered trademark) F-1" manufactured by SK Medical Electronics Co., Ltd., and were held in the atmosphere for 2 hours at the firing temperatures shown in Tables 1 and 2 to obtain pellet-shaped and block-shaped zirconia sintered body (primary sintered body) samples.
[0129] [Production of black zirconia composite sintered body (HIP-treated sintered body)] The pellet-shaped and block-shaped zirconia sintered bodies (primary sintered bodies) obtained were subjected to a Kobe Steel, Ltd. HIP device "O2-Dr.HIP" using argon gas as a pressure medium, and held at 150 MPa for 2 hours under the conditions of the HIP temperature and the presence or absence of Refer Thermo shown in Tables 1 and 2, to obtain pellet-shaped and block-shaped black zirconia composite sintered bodies (HIP-treated sintered bodies). The pellet-shaped samples obtained were 15 mm in diameter x 1.2 mm in thickness, and the block-shaped samples were 15.7 mm in width x 16.5 mm in length x 14.5 mm in height.
[0130] The content of each component of the sintered body in Tables 1 and 2 is a value calculated from the amount of raw material charged. The contents (mol %) of the capping elements or ions in Tables 1 and 2 are externally added rates relative to a total of 100 mol % of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5. The content (mol%) of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5 in Tables 1 and 2 is the content of each component in a total of 100 mol% of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5. Only ZrO2 and HfO2 are shown as the total content of ZrO2 and HfO2. The contents (mass %) of TiO2 and Al2O3 in Tables 1 and 2 are externally added rates relative to the total of 100 mass % of ZrO2, HfO2, the stabilizer, Nb2O5, and Ta2O5. In Tables 1 and 2, A / B represents the ratio of A to B when the content of Y2O3 is A mol % and the total content of Nb2O5 and Ta2O5 is B mol %.
[0131] [Color evaluation of black zirconia composite sintered body] The pellet-shaped black zirconia composite sintered body (HIP-treated sintered body) samples (diameter about 15 mm×thickness 1.2 mm) of each of the Examples and Comparative Examples were used as they were to evaluate the color tone by the following method (n=3). Using a spectrophotometer "CM-3610A" manufactured by Konica Minolta, Inc., L*, a*, and b* were measured using the L*a*b* color system (JIS Z 8781-4:2013 Colorimetry - Part 4: CIE 1976 L*a*b* color space) with a D65 light source, measurement mode SCI, measurement diameter / illumination diameter = φ8mm / φ11mm, and the background (underlay) of the sample being white (the side opposite the measurement device with respect to the sample being white). The white background (underlay) used in the measurements was a hiding power test paper used in paint measurements as described in JIS K 5600-4-1:1999. The average values of L*, a*, and b* for each sample are shown in Tables 1 and 2.
[0132] [Strength evaluation of black zirconia composite sintered body] The biaxial bending strength of the pellet-shaped black zirconia composite sintered body (HIP-treated sintered body) samples of each Example and Comparative Example was measured as is using a universal testing machine "AGS-X" (manufactured by Shimadzu Corporation) at a crosshead speed of 1.0 mm / min in accordance with ISO6872:2015 (n=5). The average values are shown in Tables 1 and 2 as the measurement results. A strength of 300 MPa or more was considered to be acceptable.
[0133] [Method for measuring average crystal grain size in sintered body] For each of the pellet-shaped black zirconia composite sintered bodies (HIP-treated sintered bodies) of the Examples and Comparative Examples, images of the surfaces were taken with a scanning electron microscope (product name "VE-9800", manufactured by Keyence Corporation). After the grain boundaries of each crystal grain were recorded on the obtained images, the average crystal grain size was calculated by image analysis. The average crystal grain size was measured using image analysis software (product name "Image-Pro Plus", manufactured by Hakuto Co., Ltd.), the captured SEM image was binarized, the brightness range was adjusted so that the grain boundaries were clear, and the particles were recognized from the field of view (area). The crystal grain size obtained with Image-Pro Plus was the average of the lengths of the line segments connecting the outlines passing through the center of gravity determined from the outlines of the crystal grains, measured at intervals of two degrees from the center of gravity, and the average value of the crystal grain size of all the particles not overlapping the edge of the image in the SEM photograph images (three fields of view) of each Example and Comparative Example was taken as the average crystal grain size (number basis) in the sintered body. "Particles not on the image edge" refers to particles excluding those whose outlines do not fit within the screen of the SEM photograph (particles whose outlines end at the top, bottom, left, and right boundaries). The crystal grain size of all particles not on the image edge was determined by selecting the option to exclude all particles on the boundary lines in Image-Pro Plus.
[0134] The average crystal grain size of the crystal grains in the black zirconia composite sintered body of Example 3 was 2.7 μm, and the average crystal grain size of the crystal grains in the black zirconia composite sintered body of Example 8 was 2.2 μm.
[0135] [Evaluation of workability of black zirconia composite sintered body] Thirty samples of block-shaped black zirconia composite sintered bodies (HIP-treated sintered bodies) of each Example and Comparative Example were prepared by attaching a metal jig to a surface of about 15.7 mm wide x 14.5 mm high, and processed into a general anterior tooth crown shape using a CEREC system "MC-XL" (manufactured by Dentsply Sirona). Although the present invention is not specifically intended for dental use, the method is suitable for evaluating the degree of workability of sintered bodies in terms of both processing time and number of pieces, so the processing test was performed on an anterior tooth shape using a dental processing machine. The processing program used was the software "inLab (registered trademark) CAM version 20.0.1.203841", and the following settings were selected: Manufacturer: IVOCLAR VIVADENT, Material name: IPS e.max CAD, Production Method: Grinding, Block size: C16, and the processing tools used were Step Bur 12 and Cylinder Pointed Bur 12S.
[0136] [Processing time] The processing times shown in Tables 1 and 2 are the times required to complete processing of the first sample using new processing tools under the conditions described in the above [Processability evaluation of black zirconia composite sintered body]. When not even one sample could be processed even after 120 minutes or more, it was marked as "X". In addition, if an error occurred due to the load during processing, etc., and the CEREC system "MC-XL" stopped midway through processing, a new processing tool was attached and processing was restarted. This operation was repeated until processing of one sample was completed, and the time required was recorded as the processing time.
[0137] [Number of pieces] The number of processed pieces shown in Tables 1 and 2 is the number of samples that could be processed into the shape of a front tooth crown without changing the processing tool once, using a new set of processing tools and starting processing of the samples under the conditions described in the above [Evaluation of the machinability of black zirconia composite sintered body]. The maximum number of samples used for the test was 30, and if processing of up to 30 samples could be completed with one processing tool, additional processing tests were not performed, and the number was uniformly set to "30 or more." Furthermore, if an error occurs due to the load during processing, etc., before the first sample is processed, and the MC-XL stops midway through processing, a new processing tool is attached and processing is resumed. This operation is repeated until one sample is processed, and the reciprocal of the number of processing tools used is taken as the number of processed samples. For example, "0.2 pieces" in Comparative Example 2 in Table 2 means that five processing tools were used to obtain a sample processed into the crown shape of one front tooth. The results are shown in Tables 1 and 2 below.
[0138] [Table 1]
[0139] [Table 2]
[0140] From the above results, it was confirmed that the black zirconia composite sintered body of the present invention has excellent machinability even though it is in a sintered state. It was also confirmed that the black zirconia composite sintered body of the present invention has suitable strength. In addition, in Examples 1 to 17, it was possible to suppress wear of the processing tool, and to increase the number of workpieces that can be continuously processed with one processing tool compared to the conventional technology. On the other hand, in Comparative Example 1, which did not contain Nb2O5 and Ta2O5, machining was not possible. In Comparative Example 2, which did not contain any capping elements or ions, the reduction in processing time was not sufficient, and the number of processed pieces was also very small. In Comparative Example 3, which contained a divalent metal element that is not included in the capping elements, the reduction in processing time was not sufficient. In Comparative Example 4, which contained a trivalent metal element that is not included in the capping elements, the reduction in processing time was not sufficient.
[0141] In addition, Patent Document 4 shows that when the amount of TiO2 added is increased, the strength decreases in proportion to the amount added (FIG. 7 of Patent Document 4). However, when Nb2O5 and / or Ta2O5 are contained as components in the black zirconia composite sintered body of the present invention, it has been confirmed from a comparison between Examples 4 and 5 that TiO2 acts integrally by further containing a capping element or ion, thereby enabling the strength of the black zirconia composite sintered body to be improved. [Industrial Applicability]
[0142] The black zirconia composite sintered body of the present invention has excellent machinability and exhibits a black color with excellent designability. [Explanation of symbols]
[0143] 1 Zirconia particles 2. Peeling ingredients 3 Adhesive component 4 Grain boundaries where no exfoliation components exist
Claims
1. ZrO 2 and HfO 2 a stabilizer capable of suppressing the phase transition of zirconia; and Nb 2 O 5 And / or Ta 2 O 5 and ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 In a total of 100 mol%, ZrO 2 and HfO 2 The total content is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, Nb 2 O 5 and Ta 2 O 5 The total content of is 1 to 9 mol%, Further comprising an element or ion derived from a capping agent, The stabilizer is Y 2 O 3 Including, the element or ion from the capping agent comprises at least one element or ion thereof selected from the group consisting of Cu, Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl, and F; The content of the element or ion derived from the capping agent is ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 More than 0 mol% and 5 mol% or less with respect to the total of 100 mol%. A sample having a diameter of 15 mm and a thickness of 1.2 mm is used to measure the color of the sample against a white background using the L*a*b* color system. The color saturation C* calculated from a* and b* is 10 or less. Black zirconia composite sintered body.
2. The content of the element or ion derived from the capping agent is ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 The black zirconia composite sintered body according to claim 1, wherein the content of each of the above is 0.05 mol% or more and 5 mol% or less with respect to a total of 100 mol%.
3. 3. The black zirconia composite sintered body according to claim 1, wherein a sample having a diameter of 15 mm and a thickness of 1.2 mm is used to measure the color of the sample against a white background in the L*a*b* color system, and the color saturation C* calculated from a* and b* is 8 or less.
4. 3. The black zirconia composite sintered body according to claim 1, wherein the colorimetric values of a sample having a diameter of 15 mm and a thickness of 1.2 mm measured against a white background in the L*a*b* color system satisfy L*≦60, |a*|≦3, and |b*|≦3.
5. 3. The black zirconia composite sintered body according to claim 1, wherein the element or ion derived from the capping agent includes at least one element or ion thereof selected from the group consisting of Cu, Ag, Li, Na, K, Rb, Cs, Fr, I, Br, Cl, and F.
6. The content of the stabilizer is expressed as Amol%, and Nb 2 O 5 and Ta 2 O 5 When the total content is B mol%, The black zirconia composite sintered body according to claim 1 or 2, wherein A / B is 0.9 or more and 3 or less.
7. The composition further comprises a zirconia reinforcement agent, and the content of the zirconia reinforcement agent is ZrO 2 and HfO 2 and the stabilizer, and Nb 2 O 5 and Ta 2 O 5 The black zirconia composite sintered body according to claim 1 or 2, wherein the content of the zirconia composite sintered body is more than 0 mass% and 5.0 mass% or less with respect to 100 mass% of the total of the zirconia composite sintered body and the black zirconia composite sintered body.
8. The zirconia reinforcement agent is TiO 2 And / or Al 2 O 3 The black zirconia composite sintered body according to claim 7, comprising:
9. The zirconia reinforcement agent is TiO 2 Including TiO 2 The black zirconia composite sintered body according to claim 8, wherein the content of is 0.6 to 3.7 mass%.
10. ZrO 2 and HfO 2 a stabilizer capable of suppressing the phase transition of zirconia; and Nb 2 O 5 And / or Ta 2 O 5 and ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 In a total of 100 mol%, ZrO 2 and HfO 2 The total content is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, Nb 2 O 5 and Ta 2 O 5 The total content of is 1 to 9 mol%, producing a molded body using a raw material composition further containing a capping agent; and sintering the compact. The step of sintering the molded body includes a step of reducing and firing the molded body, The stabilizer is Y 2 O 3 Including, the element or ion from the capping agent comprises at least one element or ion thereof selected from the group consisting of Cu, Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl, and F; The content of the element or ion derived from the capping agent is ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 More than 0 mol% and 5 mol% or less with respect to the total of 100 mol%. In the obtained black zirconia composite sintered body, a sample having a diameter of 15 mm and a thickness of 1.2 mm is used to measure the color of the sample against a white background in the L*a*b* color system. The color saturation C* calculated from a* and b* is 10 or less. The method for producing the black zirconia composite sintered body according to claim 1 or 2.
11. the capping agent contained in the raw material composition is a compound capable of becoming a monovalent ion, The method further includes a step of wet-mixing each of the raw materials of the raw material composition in a solvent containing water to obtain a raw material composition. The method for producing the black zirconia composite sintered body according to claim 10.
12. In the raw material composition, the stabilizer is ZrO 2 and HfO 2 The method for producing a black zirconia composite sintered body according to claim 10, further comprising a stabilizer that is not solid-dissolved in the zirconia composite sintered body.
Citation Information
Patent Citations
Preparation method of high-toughness and high-strength black zirconia ceramic material
CN112500159A
Black-colored free-cutting ceramics, its manufacturing method and use thereof
JP2001354480A
Black zirconia sintered compact, raw material powder for the same, and method of manufacturing them
JP2006342036A
Machinable zirconia and method for producing the same
JP2015127294A
Black zirconia sintered body and use therefor
JP2017077976A
